UPDATE STATUS DAN NAMA FACEBOOK DENGAN PERILAKU NARSISTIK - Wakhiatul Ummah; Estalita Kelly (Ilmu Psikologi Universitas Yudharta Pasuruan, 2017)
The development of increasingly sophisticated telecommunication equipment so that many people who utilize modern telecommunications facilities such as internet. One of the most popular sites is Facebook. People use Facebook to show the activities performed to be seen by others. The facebook users who write down all activities without a specific intention to deliberately to gain the attention of others. The purpose of this study to determine the relationship between status updates and the facebook account with attention seeking behavior called narcissistic behavior. The subjects used are facebook users as many as 100 people. Narcissistic behavior is measured using a narcissistic behavior scale. The result of the research is there is a significant relationship between status updates and name of facebook with narcissistic behavior (rx1x2y = 0,225 with rtable 1% = 0,256 and rtable5% = 0,195).